The role of delamanid in the treatment of drug-resistant tuberculosis - Lewis JM; Sloan DJ (Dove Medical Press, 2015)
Joseph M Lewis,1 Derek J Sloan2,3 1Tropical and Infectious Disease Unit, Royal Liverpool University Hospital, Liverpool, UK; 2Liverpool School of Tropical Medicine, Pembroke Place, Liverpool, UK; 3Liverpool Heart and Chest Hospital, Liverpool, UK Abstract: Tuberculosis (TB) remains a significant cause of death worldwide, and emergence of drug-resistant TB requires lengthy treatments with toxic drugs that are less effective than their first-line equivalents. New treatments are urgently needed. Delamanid, previously OPC-67863, is a novel drug of the dihydro-nitroimidazole class with potent anti-TB activity and great promise to be effective in the treatment of drug-resistant TB. This review examines the preclinical and clinical development of delamanid, reviews current guidance on its use and evaluates the opportunities and challenges for its future role in TB management. Keywords: delamanid, OPC-67683, tuberculosis, drug resistance, MDR-TB